Gema Nusantara Pelajar Music Community: Violin Learning Methods and Its Role in Developing Musical Talent in Semarang - Wynsa, Elsya; Harmono Sejati, Irfanda Rizki (Universitas Negeri Surabaya, 2025)
This study reveals the violin learning method in the Gema Nusantara Pelajar Semarang music community and the role of the community in developing the musical talents of its members. The right learning method has a significant impact on achieving learning outcomes, enhancing the quality of the learning process, and motivating learners. This study employed a qualitative approach, where data were collected through interviews, direct observation, and document review. The participants of this study were instructors, community members, and parents. The results of the study indicate that a series of learning methods used, such as the Suzuki method, inquiry method, demonstration method, drill method, project method, and cooperative method have effectively improved the ability of community members to play the violin, both in terms of skill and musicality. The Gema Nusantara Pelajar Community is not only a place to gather and practice the violin, but its active role in holding concerts and masterclasses can be a means for the community to develop the talents of its members. This study emphasizes that developing talent does not only rely on the right learning method but also requires an active role and cooperation from members and founders of the community.